A case report of neuronal intranuclear inclusion disease with paroxysmal peripheral neuropathy-like onset lacking typical signs on diffusion-weighted imaging - Fu, Jiayu; Zhao, Chen; Hou, Guanghao; Liu, Xiaoxuan; Zheng, Mei; Zhang, Yingshuang; Zhang, Shuo; Zheng, Danfeng; Zhang, Yixuan; Huang, Xiao; Ye, Shan; Fan, Dongsheng (Frontiers in Neurology, 2023)
Background Neuronal intranuclear inclusion disease (NIID) is a slowly progressive neurodegenerative disease characterized by eosinophilic hyaline intranuclear inclusions and the GGC repeats in the 5'-untranslated region of NOTCH2NLC. The prevalent presence of high-intensity signal along the corticomedullary junction on diffusion-weighted imaging (DWI) helps to recognize this heterogeneous disease despite of highly variable clinical manifestations. However, patients without the typical sign on DWI are often misdiagnosed. Besides, there are no reports of NIID patients presenting with paroxysmal peripheral neuropathy-like onset to date. Case presentation We present a patient with NIID who suffered recurrent transient numbness in arms for 17 months. Magnetic resonance imaging (MRI) showed diffuse, bilateral white matter lesions without typical subcortical DWI signals. Electrophysiological studies revealed mixed demyelinating and axonal sensorimotor polyneuropathies involving four extremities. After excluding differential diagnosis of peripheral neuropathy through body fluid tests and a sural nerve biopsy, NIID was confirmed by a skin biopsy and the genetic analysis of NOTCH2NLC. Conclusion This case innovatively demonstrates that NIID could manifest as paroxysmal peripheral neuropathy-like onset, and addresses the electrophysiological characteristics of NIID in depth. We broaden the clinical spectrum of NIID and provide new insights into its differential diagnosis from the perspective of peripheral neuropathy.